2007
DOI: 10.1111/j.1474-919x.2007.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult sex ratios in wild bird populations

Abstract: Offspring sex ratios in wild bird populations, and the extent to which they vary from the equality expected by random genotypic sex determination, have received much recent attention. Adult sex ratios (ASRs) in wild birds, on the other hand, remain very poorly described, and many of the questions about them posed by Ernst Mayr in 1939 remain unanswered. This review assesses population-level sex ratio patterns in wild bird populations, with an emphasis on the ASR. A quantitative assessment of over 200 published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
568
3
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(610 citation statements)
references
References 258 publications
(457 reference statements)
24
568
3
15
Order By: Relevance
“…Furthermore, different detectability of the sexes, a potential confound of field estimates of ASR 19 , is not likely to bias our results: the more polygamous sex is expected to be more conspicuous because of elaborate plumage, displays and general activity 2 , which would potentially bias ASR estimates towards the direction opposite to our findings (that is, biasing ASR estimates towards the polygamous sex).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, different detectability of the sexes, a potential confound of field estimates of ASR 19 , is not likely to bias our results: the more polygamous sex is expected to be more conspicuous because of elaborate plumage, displays and general activity 2 , which would potentially bias ASR estimates towards the direction opposite to our findings (that is, biasing ASR estimates towards the polygamous sex).…”
Section: Resultsmentioning
confidence: 61%
“…We tested whether ASR predicts mating systems and parental care using Phylogenetic Generalized Least Squares 17,18 . Although data on ASR from wild populations are difficult to obtain 19 , the information now available for shorebirds permits tests of the theoretical predictions using statistically robust sample sizes.…”
mentioning
confidence: 99%
“…Clutton-Brock et al (1985) and Clutton-Brock and Isvaran (2007) note that in dimorphic mammalian species there is a very female biased ASR, due to the fact that males take longer to mature and male-male competition leads to a higher rate of mortality among adult males than among adult females. Liker and Székely (2005) and Donald (2007) observe that in most bird species there tends to a more balanced ASR than in mammalian species. Also, in avian species where just female care is observed the ASR tends to be female biased.…”
Section: This Leads Tomentioning
confidence: 99%
“…Demography and genetic structure in parrotbills Donald, 2007). Firstly, this study has shown that adult survival rate is low, but also extremely variable among years (Table 1).…”
Section: Discussionmentioning
confidence: 99%